SELERA PENDUDUK KOTA TERHADAP FAST FOOD (STUDI KASUS KONSUMEN 7SEVENCHICKEN MALANG, INDONESIA) - M. Zul Mazwan; Musta’in Islami Imran; Gumoyo Mumpuni (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2022)
The current era of information technology and globalization brings many changes in people's lives, including changes in life style, especially in consumption patternsso that the concept of serving food instantly emerged, that is practical and efficient in time, taste and affordable prices, namely fast food. The aims of this study are (1) knowing the characteristics of fast-food consumers in Malang, (2) knowing the main factors that are considered the most important by consumers in consuming fast food in Malang, (3) knowing consumer preferences for fast food in Malang. The sampling technique used a combination of accidental sampling and purposive sampling methods to obtain 100 respondents. The analytical method used descriptive analysis and conjoint analysis. Consumers who consume fast food dominated by male gender and the majority are students, they are in the age range of 20 to 24 years old and come from the East Java region. Most consumers have an allowance of Rp1.000.000 to Rp1.500.000 per month. Based on the conjoint analysis, it is known that the main factors that are considered the most important by consumers in making a purchase are the product factor, packaging, facilities and price factor. Consumer preferences choose prices ranging from Rp20.000 to Rp30.000. Regarding to the packaging variable, consumers prefer large packages. The facility which is preferred by consumers is co-working space facility and the product that is most favored by consumers is processed chicken products.